دور القوة الانفجارية في تنمية صفة الارتقاء لدى لاعبي كرة الطائرة - طهير, ياسمين; زواق, عادل (جامعة الوادي - University of Eloued, 2020)
تهدف الدراسة الحالية إلى تحليل وإبراز أهمية القوة الانفجارية في تنمية صفة الارتقاء للاعبي كرة الطائرة، وإلقاء الضوء على جانب مهم من جوانب التدريب البدني الذي ينمي القدرات المهارية والبدنية للاعب كرة الطائرة ويحسن مستواه. إن لدراسة الإشكالية المطروحة وتأكيد أو نفي الفرضية لا يمكن أن يتحقق إلا من خلال إتباع منهجية أو خطة علمية واستجابة لطبيعة بحثنا فإننا اعتمدنا على المنهج الشبه التجريبي ذات المجموعة التجريبية فقط الذي يسمح لنا بالتحقق من دور القوة الانفجارية في تنمية صفة الارتقاء عند لاعبي كرة الطائرة، استخدمنا اختبار سارجنت ،آلة حاسوب، شريط قياس، ورقة مدرجة أو عصى مترية حائط )بارتفاع مناسب(، سلم، وعاء به ماء ملون كوسائل وأدوات للبحث، تم اختيار العينة بطريقة مقصودة وذلك لإيجاد أحسن النتائج وأفضل الوسائل التدريبية، والتدريب المنتظم دون الانقطاع، وعلى هذا الأساس تم اختيار 16 لاعب ينشطون في فريق وداد الرويبة بالجزائر صنف أشبال، أما فيما يخص الأساليب الإحصائية فقد تم الاعتماد على حساب التكرار والمتوسط الحسابي والانحراف المعياري، اختبار ت، أظهرت نتائج الدراسة أن للقوة الانفجارية دور ايجابي في تنمية صفة الارتقاء لدى لاعبي كرة الطائرة.. The present study aims to analyze and highlight the importance of explosive power in developing the upgrading qualities of volleyball players and shed light on an important aspect of physical training which develops and improves the skill and physical abilities of the volleyball player. The study of the problem presented and the confirmation or denial of the hypothesis can not be achieved only through a scientific methodology or plan and in response to the nature of our research, we relied on the semi-experimental method of experimental group only, which allows us to verify the role of explosive power in the development of upgrading qualities of volleyball players, We used the Sargent test, a computer machine, a measuring tape, a sheet of paper or a wall meter (a suitable height), a ladder, a pot with colored water as a means and tools for research, the sample was chosen in a deliberate manner to find the best results and the best training methods, regular training without interruption, This is S has been selected 16 players are active in the team and Dad Rouiba in Algeria class cubs, either with regard to statistical methods have been relying on the repetition and the arithmetic mean of the standard deviation calculation, t test, the results of the study showed that the explosive force a positive role in the character of upgrading the players of volleyball development.
مقال
Keywords: القوة الانفجارية، كرة الطائرة، الارتقاء، التدريب الرياضي; explosive force, volleyball, elevation, sports training